The Complex World of Regulation of Pituitary Growth Hormone Secretion: The Role of Ghrelin, Klotho, and Nesfatins in It - Devesa, Jesús (Frontiers in Endocrinology, 2021)
The classical concept of how pituitary GH is regulated by somatostatin and GHRH has changed in recent years, following the discovery of peripheral hormones involved in the regulation of energy homeostasis and mineral homeostasis. These hormones are ghrelin, nesfatins, and klotho. Ghrelin is an orexigenic hormone, released primarily by the gastric mucosa, although it is widely expressed in many different tissues, including the central nervous system and the pituitary. To be active, ghrelin must be attached to an n-octanoyl group (n=8, generally) on serine 3, forming acyl ghrelin which is then able to bind and activate a G-protein- coupled receptor that leads to the activation of phospholipase C that induces the formation of inositol 1,4,5-triphosphate and diacylglycerol that produce an increase in cytosolic calcium that allows the release of GH. In addition to its direct action on somatotrophs, ghrelin co-localizes with GHRH in several neurons, facilitating its release by inhibiting somatostatin, and acts synergistically with GHRH stimulating pituitary GH synthesis and secretion. Gastric ghrelin production declines with age, as does GH. Klotho is an anti-aging agent, produced mainly in the kidneys, whose soluble circulating form directly induces GH secretion through the activation of ERK1/2 and inhibits the inhibitory effect exerted by IGF-I on GH. Untreated GH-deficient children and adults show reduced plasma levels of klotho, but GH treatment restores them to normal values. Deletions or mutations of the Klotho gene affect GH production. Nesfatins 1 and 2 are satiety hormones, they suppress food intake; they have been found in GH3 cell cultures where they significantly reduce the expression of GH mRNA and that of the pituitary-specific positive transcription factor 1, consequently acting as inhibitors of GH production. This is a consequence of the down-regulation of the cAMP/PKA/CREB signaling pathway. Interestingly, nesfatins eliminate the strong positive effect ghrelin has on GH synthesis and secretion. Throughout this review, we will try to broadly analyze the role of these hormones in the complex world of GH regulation, a world in which these hormones already play a very important role.